The Role of the Media in Forming the Political Thinking of Youth - Akramkulovich, Saidkulov Nuriddin (Researchparks Publishing, 2023)
this article is written about the negative or positive influence of the mass media, especially the Internet, on the spiritual development of society, on the personality, especially on the worldview of young people, and on their ideological education. In today's time, when you can access the world's media space through mass media, the impartiality and correctness of information affects the image of countries in the international arena. In this respect, it is impossible to make a mistake in the information policy. It is very important to develop a mechanism to protect against various harmful information in the information space, especially when it comes to the mind and worldview of young people.